Proposition of a modeling and an analysis methodology of integrated reverse logistics chain in the direct chain - Faycal Mimouni; Abdellah Abouabdellah (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: Propose a modeling and analysis methodology based on the combination of Bayesian networks and Petri networks of the reverse logistics integrated the direct supply chain. Design/methodology/approach: Network modeling by combining Petri and Bayesian network. Findings: Modeling with Bayesian network complimented with Petri network to break the cycle problem in the Bayesian network. Research limitations/implications: Demands are independent from returns. Practical implications: Model can only be used on nonperishable products. Social implications: Legislation aspects: Recycling laws; Protection of environment; Client satisfaction via after sale service. Originality/value: Bayesian network with a cycle combined with the Petri Network.
Keywords: 650; reverse logistics; processes; graphical modeling; uncertainty; Petri network; Bayesian network